Designing a Democratic Education Curriculum through History Learning for High School Students - Zulkarnain; Dimas Aldi Pangestu; Muhammad Amirrudin; Gunartati (Paramita: Historical Studies Journal, 2025)
Abstract: The purpose of this research is to discover the capabilities of history teachers in designing the internalization plan for democratic values in history lectures; to understand the implementation process of democratic values in history subjects; and to discover the obstructions in implementing those values in high school. This research uses a qualitative research method with a descriptive approach. Data were collected through interviews with three history teachers and twenty students, classroom and school observations, and document analysis at SMAN 2 Ngaglik, a public high school in Yogyakarta, Indonesia. The data was then analyzed using the interactive data analysis technique: data reduction, presentation, and conclusion. This research shows democratic education can be applied and assessed concretely in an inclusive and diverse learning environment, using history as a vehicle for developing democratic capacity and forming inclusive citizenship. These thematic findings illustrate a comprehensive approach to democracy education at SMAN 2 Ngaglik, which integrates inclusivity, student-centered pedagogy, civic engagement, tolerance, responsibility, and the use of technology through historical curriculum design and practice. Approaches in schools provide valuable insights and examples for designing inclusive democratic curricula that align with global efforts to develop participatory, tolerant, and autonomous citizens through education. History education can be used as a model of inclusive democratic education closely linked to student diversity and technological innovation, providing valuable new insights and a practical framework for application in pluralistic educational environments. Abstrak: Tujuan penelitian ini adalah untuk mengetahui kemampuan guru sejarah dalam merancang rencana internalisasi nilai-nilai demokrasi dalam pembelajaran sejarah; memahami proses penerapan nilai-nilai demokrasi dalam mata pelajaran sejarah; serta mengidentifikasi hambatan dalam penerapan nilai-nilai tersebut di sekolah menengah atas. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Data dikumpulkan melalui wawancara dengan tiga guru sejarah dan 20 siswa, observasi di kelas dan lingkungan sekolah, serta dokumentasi di SMA Negeri 2 Ngaglik. Data kemudian dianalisis dengan teknik analisis interaktif yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pendidikan demokrasi dapat diterapkan dan dievaluasi secara konkret dalam lingkungan belajar yang inklusif dan beragam, dengan menjadikan pelajaran sejarah sebagai sarana pengembangan kapasitas demokratis dan pembentukan kewarganegaraan yang inklusif. Temuan-temuan tematik ini menggambarkan pendekatan komprehensif terhadap pendidikan demokrasi di SMA Negeri 2 Ngaglik yang mengintegrasikan nilai inklusivitas, pedagogi berpusat pada siswa, partisipasi warga, toleransi, tanggung jawab, serta pemanfaatan teknologi melalui desain dan praktik kurikulum sejarah. Pendekatan di sekolah ini memberikan wawasan dan contoh berharga dalam merancang kurikulum demokrasi yang inklusif dan selaras dengan upaya global untuk membentuk warga negara yang partisipatif, toleran, dan mandiri melalui pendidikan. Pendidikan sejarah dapat dijadikan model pendidikan demokrasi inklusif yang terkait erat dengan keberagaman siswa dan inovasi teknologi, serta memberikan wawasan baru yang berharga dan kerangka praktis untuk diterapkan di lingkungan pendidikan yang pluralistik.